(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
his article attempts to be a contribution to the training of history teachers. It reviews various aspects of historical epistemology to explore its educational possibilities. he article insists on the idea that history should ofer symbolic tissues that permit the student to give meaning to their experiences. For this it is important to avoid certain barriers that arise from scientiic history and pedagogy, such as the foreclosure of the subject, overinterpretation, the abuse of rigid designators and the displacement of the desire of enjoyment. he article starts from a poststructuralist theoretical and conceptual framework and frequently uses Lacanian thought. It emphasizes the importance of the subjective localization and indicates as its principal objective the didactics of history to contribute to the emergence to an historic subject.